2001
DOI: 10.1038/sj.gt.3301483
|View full text |Cite
|
Sign up to set email alerts
|

Reduced growth in response to ganciclovir treatment of subcutaneous xenografts expressing HSV-tk in the vascular compartment

Abstract: Using a recombinant retrovirus with ecotropic envelope we have achieved high efficiency of transduction of endothelial cells in the vasculature of subcutaneous xenografts arising from the co-injection of tumour cells and irradiated virus producers. We have used this experimental system to assess the efficacy of the herpes simplex virus-thymidine kinase (HSV-tk)/ganciclovir (GCV) prodrug activation system in anti-vascular therapy. Treatment of KSY-1 xenografts with HSV-tk transduction in the vascular compartmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Three previous studies reported the effectiveness of TK targeting in tumor endothelium as antitumoral strategy. [50][51][52] In two cases, 50,51 TK was also expressed in tumor cells as nonspecific promoters were used. In the experimental model established by Mavria and Porter, 52 the ecotropic retrovirus expressing TK could only infect the vasculature and not the human tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three previous studies reported the effectiveness of TK targeting in tumor endothelium as antitumoral strategy. [50][51][52] In two cases, 50,51 TK was also expressed in tumor cells as nonspecific promoters were used. In the experimental model established by Mavria and Porter, 52 the ecotropic retrovirus expressing TK could only infect the vasculature and not the human tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52] In two cases, 50,51 TK was also expressed in tumor cells as nonspecific promoters were used. In the experimental model established by Mavria and Porter, 52 the ecotropic retrovirus expressing TK could only infect the vasculature and not the human tumor cells. This latter study illustrates the relevance of vascular TK expression in tumor growth reduction, compared to tumor cell transduction alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial cells are normally quiescent but become activated in tumours, 8 rendering them sensitive to infection, and we have demonstrated that herpes simplex virus thymidine kinase (TK) expression in tumour vasculature followed by the administration of the prodrug ganciclovir can significantly reduce the growth of tumour xenografts. 9 Multiple levels of vector specificity can be envisaged, such as the use of modified envelope proteins or the expression of a specific therapeutic product. In this study, we have focused on the introduction of endothelial cell-specific transcriptional control.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 The dependence of tumours on a vascular network for growth and the greater accessibility of vessels compared to tumour cells make this an attractive target for gene therapy. To this end, we are developing vectors for systemic delivery to target tumour vasculature.…”
Section: Introductionmentioning
confidence: 99%